Bringing Jails into the Twenty-First Century: Evaluating Jail TV as a Method for Programming. Issue 2 (15th March 2022) - Garman, Julie D.; Cooley, Brooke N.; Foxall, Mark; Sample, Lisa L.
ABSTRACT: Jails serve a valuable role in the American correctional system. Historically, the quick turnover in population and limited resources that plague jails create impediments to the delivery of programming content for inmates. A large Midwestern jail facility has sought to increase inmate exposure to evidence-based cognitive behavioral programming through the use of a facility-wide CCTV system, known as Jail TV. This outcome evaluation discusses the program's effects on the short-term goals of the facility and program administrators. Facility data suggests that the use of Jail TV increases the amount of programming delivered to more inmates, as well as increasing inmate awareness of facility and community resources that are beneficial upon reentry into the community. Finally, researchers discuss the implications Jail TV has for changing the way correctional facilities think about the delivery of treatment and programming options.